A Comparative Analysis of Rationalism Paradigms: An Islamic and Western Perspective - Hasanah Harahap, Nurizka; Khudori Soleh, Achmad (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the concept of rationalism from both Islamic and Western perspectives through a comparative approach. Previous research indicates that the two traditions share the use of reason as an epistemic instrument, yet differ significantly in their sources of truth, methodological foundations, and philosophical orientations. This research employs a library-based method with a philosophical-descriptive approach to examine the ideas of key thinkers from both traditions. The findings reveal that Western rationalism grounds truth in the autonomy of human reason through deductive methods, methodological skepticism, and the coherence theory of truth. In contrast, Islamic rationalism integrates reason with divine revelation, particularly in interpreting theological and metaphysical realities. These distinctions influence the development of scientific thought, the structure of epistemology, and ethical orientations within each civilization. This study concludes that Islamic rationalism is characterized by a theocentric-integrative framework, whereas Western rationalism tends to be anthropocentric and secular. The results of this research are expected to contribute to the discourse on comparative epistemology and provide a foundation for further studies on the integration of knowledge.